USO DE PLASMA DE DOADOR CONVALESCENTE PARA TRATAR PACIENTES COM INFECÇÃO GRAVE PELO SARS-COV-2 (COVID-19) - GHISLAINE GONÇALEZ DE ARAUJO ARCANJO (2022)
COVID-19 is a potentially fatal disease without specific therapy. Evidence suggests that convalescent plasma (CCP) may be useful against severe cases of SARS-CoV-2. Methods: Multicenter, randomized, controlled Clinical Trial in five hospitals in Brazil between April and December 2020, to assess whether high-dose CCP transfusion can benefit critically ill patients with COVID-19. Critically ill patients hospitalized within 10 days of symptom onset were eligible. The study was designed for a sample size of 120 participants. Three daily doses (600 mL each) of CCP transfusion (neutralizing antibody titer ≥ 64) were added to standard treatment, for the group randomized as Plasma group, the Control group received no additional treatment. The primary outcomes were the 30- and 60-day mortality rate. Secondary outcomes were days without mechanical ventilation and days without hospitalization evaluated respectively at 30 and 60 days after randomization. Results and discussion: One hundred and ten participants were enrolled and three were later excluded. Among the 107 participants evaluated, 36 were randomized to receive CP and 71 to the control group. Mean ages between groups were 56 ± 15 years (CCP) and 59 ± 12 years (control). Mortality rates were 22% in CCP and 25% in the control group (OR 0.84; 95% CI, 0.32-2.25; P = 0.81) on day 30 and 31% (CCP) and 35% (control) (OR 0.81; 95% CI, 0.35-1.86; P = 0.67) on day 60. The number of days free from mechanical ventilation in the 30-day assessment were 12.5 (CCP; range, 0-30) and 12 (control; 0-30; P = 0.82) and 42.5 (CCP; 0-60) and 39 (control; 0-60; P = 0 .80) on day 60. The length of hospital stay was not different between groups (P = 0.43). CCP transfusion had no significant impact on serum inflammatory markers. Conclusion: The addition of high-dose CCP to support the care of patients with severe COVID-19 did not bring benefits in reducing mortality, nor did it reduce the length of hospital stay or mechanical ventilation. Keywords: Neutralizing Antibodies. COVID-19. Coronavirus Infection. Passive Immunization. SARS-CoV-2.